Behaviour of different passionfruit plants related to the root-knot nematode - Klein, Aldo Luiz; Ferraz, Luiz Carlos Camargo Barbosa; Oliveira, João Carlos de (Pesquisa Agropecuaria Brasileira, 2014)
This paper deals with the behaviour of different passionfruit species when inoculated with the root-knot nematode Meloidogyne incognita. Evaluations were made 80 days after inoculation with the nematode, based on number of gall and oothecas observed on the root systems of the plants. Passiflora alata, P. giberti, P. maliformis, and P. serrato digitate were considered highly susceptible, whereas P. caerulea, P. edulis and P. edulis f. flavicarpa showed high resistance.